United Kingdom : Financial Sector Assessment Program-Property Markets and Financial Stability-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
The main purpose of this paper is to assess the risks to the financial sector that currently emanate from the United Kingdom property markets. The interaction of property markets with financial markets has important implications for financial stability. Cycles in the prices of housing and commercial property affect the balance sheets of households, banks, and other financial institutions. Excessive lending and price swings in property markets can cause significant distress to both borrowers and lenders. A drop in prices of real property weights on firms' access to finance, which can reduce economic activity, leads to further declines in asset prices and potential financial stability risks.